Stres Kerja Pada Pegawai Kantor Rehabilitasi Sosial Di Dinas Sosial Kota Surakarta - Aldila Andari Kristi; Sri Ernawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The author conducted this research to answer and understand the work stres experienced by employees of the social rehabilitation office at the Surakarta social service. This type of research uses qualitative. The sample studied was 4 employees. The data collection mothod uses interviews to reveal the work stres that is being experienced. Work stres is a very important occupational health problem, which can cause physical illness to the point of death, and can affect work well-being and productivity.